Hand and upper extremity anatomy to color and study (Hanley & Belfus, 2000)
This comprehensive, interactive atlas is an expansion from the arm section of Dr. Poritsky's "Anatomy to Color and Study" with the inclusion of many more drawings. The book's purpose is to supplement and reinforce the student's knowledge of hand and arm anatomy by the coloring and lebeling of key structures. Examples are given to help describe muscles in terms of their origin, insertion, action, and innervation. There are a total of 78 drawings depicting various aspects of the fingers, hand, wrist, elbow, and shoulder.